Elision of Glottal Consonants in Kalhori Kurdish Names - Mehdi Fattahi (مطالعات زبان‌‌ها و گویش‌های غرب ایران, 2020)
Persian and Kalhori Kurdish, display some differences in the phonetic forms of names containing glottal consonants. This article attempts to analyze the deletion of glottal consonants of post-vocalic /h/ and /ʔ/. The data was collected through interviews with 10 native speakers of Kalhori Kurdish, and the names with different pronunciations from those of Persian were identified. One of the big differences between Persian and Kurdish in this regard lies in the sequence of a vowel and a glottal consonant. Kalhori Kurdish drops the glottal consonant and modifies vowels in order to save the syllable weight. After the elision of the glottal consonant, the vowel preceding it meets either another vowel or a consonant. This article investigates the cases in which the vowel meets a consonant. When the vowel meets a consonant, three processes of replacement of the short vowel with a long one, lengthening the short vowel, and vowel harmony may occur. This article attempts to explain these changes in Optimality Theory. The analysis of the data shows the dominance of the markedness constraint of *V/GLOT over the faithful constraint IDENT(V). These changes are allowed to take place as long as the vowel system of Kalhori Kurdish permits it.